Correlation of Islamic Spirituality in Reducing Student’s Delinquency Problems - Padzil, Ruhaiza Binti; Yusoff, Mohd Zailani Mohd; Kasa, Muhamad Dzahir (SCAD Independent, 2020)
This study aimed to identify the relationship between Islamic spirituality and the level of delinquent behavior. Islamic spirituality among students is studied in terms of belief and faith, extrinsic and intrinsic aspects. This study used the survey method. The sample of this study was selected using random sampling. Data was collected from a pilot sample of 120 Malay students studying in ordinary secondary schools in Johor using questionnaires. The research questionnaire used Islamic Spiritual Disposition Questionaire (ISDQ) developed by Mohd Zailani (2009) and Delinquency Behaviour Disposition questionnaires developed by Carl Jung’s (1997). Quantitative data were analyzed using descriptive statistics and Pearson correlation. The analysis of the study showed that there is a significant relationship between the dimensions of Islamic spirituality and the level of delinquent behavior among students. The findings of the study showed that the domains involved in Islamic spirituality may reduce the tendency of delinquent behavior among students.